Coronary artery plaque characteristics and treatment with biologic therapy in severe psoriasis: results from a prospective observational study - Elnabawi, Youssef A (Cardiovasc Res, 2019)
AIMS: The use of biologic therapy has increased over the past decade well beyond primary autoimmune diseases. Indeed, a recent trial using an anti-IL-1beta antibody reduced second myocardial infarction (MI) in those who have had MI. Psoriasis is a chronic inflammatory disease often treated with biologics when severe, is associated with increased risk of MI, in part driven by high-risk coronary plaque phenotypes by coronary computed tomography angiography (CCTA). We hypothesized that we would observe a reduction in inflammatory-driven phenotypes of coronary plaque, including non-calcified coronary plaque burden and lipid-rich necrotic core in those treated with biologic therapy after one-year compared with non-biologic therapy. METHODS AND RESULTS: In a prospective, observational study, 290 participants were recruited from 1 January 2013 through 31 October 2018 with 215 completing one-year follow-up. Of the 238, 121 consecutive participants who were biologic treatment naïve at baseline were included. A blinded reader (blinded to patient demographics, visit and treatment) quantified total coronary plaque burden and plaque subcomponents (calcified and non-calcified) in the three main coronary vessels >2 mm using dedicated software (QAngio, Medis, Netherlands). Psoriasis patients were middle-aged [mean (standard deviation) age, 50.5 (12.1) years], mostly male (n = 70, 58%) with low cardiovascular risk by Framingham score [median (interquartile range, IQR), 3 (1–6)] and had moderate to severe skin disease at baseline [median (IQR) Psoriasis Area Severity Index, PASI, 8.6 (5.3–14.0)]. Biologic therapy was associated with a 6% reduction in non-calcified plaque burden (P = 0.005) reduction in necrotic core (P = 0.03), with no effect on fibrous burden (P = 0.71). Decrease in non-calcified plaque burden in the biologic treated group was significant compared with slow plaque progression in non-biologic treated (Δ, −0.07 mm(2) vs. 0.06 mm(2); P = 0.02) and associated with biologic treatment beyond adjustment for traditional cardiovascular risk factors (β = 0.20, P = 0.02). CONCLUSION: In this observational study, we demonstrate that biologic therapy in severe psoriasis was associated with favourable modulation of coronary plaque indices by CCTA. These findings highlight the importance of systemic inflammation in coronary artery disease and support the conduct of larger, randomized trials.